RELATIONSHIP BETWEEN MUSCLE STRENGTH AND STRESS IN THE ELDERLY IN BANJAR SAMU, SINGAPADU KALER, SUKAWATI, GIANYAR, BALI. - Fajarina Lathu Asmarani; Rizky Erwanto; I Made Setia Suryawan (Jurnal Keperawatan Respati Yogyakarta, 2022)
One of the disorders in the elderly is stress. The stress elderly will have an impact on health. Stress elderly can arise because in the elderly there are changes in body composition, muscles, bones, and joints. The preliminary study showed that from 6 elderly, all elderly experienced a decrease in leg muscle strength. 2 elderly experienced mild stress. The purpose of this study was to determine the relationship between muscle strength and stress in the elderly in Banjar Samu, Singapadu Kaler, Sukawati, Gianyar, Bali. This research is non-experimental quantitative research with an analytical observational method with a cross-sectional design. The sample of this study was the elderly, as many as 46 elderly. It used the total sampling technique. Data collection tools using a questionnaire and chair stand test. Data analysis used Fisher Exact analysis. The statistical test of the relationship between muscle strength and stress showed a p-value of 0.009 <0.05. The majority of the elderly have abnormal muscle strength, namely 33 people or 71.7%, the majority of the elderly have normal stress levels, namely 33 people or 71.7%. There is a significant relationship between muscle strength and stress in the elderly in Banjar Samu, Singapadu Kaler, Sukawati, Gianyar, Bali. Keywords: Elderly; Muscle strength; Stress